2010
DOI: 10.1167/10.6.2
|View full text |Cite
|
Sign up to set email alerts
|

Motor signals in visual localization

Abstract: We demonstrate a strong sensory-motor coupling in visual localization in which experimental modification of the control of saccadic eye movements leads to an associated change in the perceived location of objects. Amplitudes of saccades to peripheral targets were altered by saccadic adaptation, induced by an artificial step of the saccade target during the eye movement, which leads the oculomotor system to recalibrate saccade parameters. Increasing saccade amplitudes induced concurrent shifts in perceived loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
93
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(113 citation statements)
references
References 39 publications
18
93
2
Order By: Relevance
“…In this view, one may argue that localization judgments and saccade targeting share a common representation. This is also supported by findings that mislocalization also occurs during periods of fixation (Garaas and Pomplun 2011;Moidell and Bedell 1988;Schnier et al 2010;Zimmermann and Lappe 2010), suggesting that saccadic adaptation affects visual localization at the target registration or planning stages.…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…In this view, one may argue that localization judgments and saccade targeting share a common representation. This is also supported by findings that mislocalization also occurs during periods of fixation (Garaas and Pomplun 2011;Moidell and Bedell 1988;Schnier et al 2010;Zimmermann and Lappe 2010), suggesting that saccadic adaptation affects visual localization at the target registration or planning stages.…”
mentioning
confidence: 54%
“…This adjustment reduces the postsaccadic visual error during subsequent trials and allows the eyes to land closer to the shifted target. The effectiveness of saccadic adaptation depends on the location, timing, and consistency of the postsaccadic error (Collins et al 2009;Havermann and Lappe 2010;Noto and Robinson 2001;Panouilleres et al 2011;Shafer et al 2000;Wallman and Fuchs 1998;Zimmermann and Lappe 2010).…”
mentioning
confidence: 99%
“…Several researches have demonstrated that the modification of motor variables by saccade adaptation leads to a distortion of visual localization of the target executed by hand pointing or by perceptual reports (Bahcall and Kowler, 1999;Awater et al, 2005;Bruno and Morrone, 2007;Collins et al, 2007, Zimmermann andLappe, 2010;Garaas and Pomplun, 2011;Gremmler et al, 2014). All these studies imply that localization of visual stimuli is based on a perceptual representation that is linked to an action representation that guides saccades and pointing.…”
Section: Introductionmentioning
confidence: 99%
“…The neural locus of saccade adaptation is not fully determined. In humans, differences in adaptation between saccade types (Deubel, 1995a;Alahyane et al, 2007;Cotti et al, 2007;Zimmermann and Lappe, 2009) and also between adaptation directions (Ethier et al, 2008;Panouillères et al, 2009;Zimmermann and Lappe, 2010) suggest that oculomotor plasticity can occur at multiple stages of the oculomotor system. Electrophysiological studies in monkeys, however, have found changes after saccade adaptation only in the oculomotor vermis of the cerebellum (Catz et al, 2008) and lower brainstem structures.…”
Section: Discussionmentioning
confidence: 99%
“…Oculomotor plasticity is paralleled by changes in visual localization that shift the apparent position of visual objects in space (Bahcall and Kowler, 1999;Awater et al, 2005;Bruno and Morrone, 2007;Collins et al, 2007). Saccadic adaptationinduced distortions of visual space have been found even during fixation, suggesting a common mechanism for saccade and visual targeting (Moidell and Bedell, 1988;Schnier et al, 2010;Zimmermann and Lappe, 2010). Modifications in saccade targeting must occur at multiple sites of the oculomotor pathways because different types of saccades (e.g., reactive or scanning saccades) show different adaptation behavior (Erkelens and Hulleman, 1993;Deubel, 1995a;Fujita et al, 2002;Collins and Doré-Mazars, 2006;Alahyane et al, 2007;Cotti et al, 2007;Zimmermann and Lappe, 2009).…”
Section: Introductionmentioning
confidence: 99%